BALANOCARPOL AND HEIMIOL A, TWO RESVERATROLS DIMER FROM STEM BARK Hopea mengarawan (Dipterocarpaceae) - Sri Atun; Nurfina Aznam; Retno Arianingrum; Masatake Niwa (Universitas Gadjah Mada, 2006)
Isolation and structure elucidation of two resveratrols dimer, namely balanocarpol (1) and heimiol A (2) from stem bark of Hopea mengarawan had been done. The isolation of those compounds was carried out by chromatographic method and structure elucidation was performed by interpretation of spectroscopic data, including UV, IR, 1H and 13C NMR 1D and 2D, and FABMS.